Dancing and Calculating: Culturally sustainable development and globalization in light of two paradigms of socio-cultural evolution - Katunarić, Vjeran (Array, 2014)
Globalization challenges the usefulness of different paradigms of socio-cultural evolution and opens the possibility for their hybridization. In this paper, two paradigms of evolution, the transformational (Spencerian) and the variational / selectionist (Darwinian), as discerned by Fracchia and Lewontin (1999), are examined along with their social theoretical counterparts. Most social theories of development are connected to different evolutionary paradigms in different historical contexts. The transformational paradigm prevailed until the end of the Cold War (e.g. theories of modernization), and the selectionist paradigm, in various theoretical forms, thereafter (e.g. Huntington, Eisenstadt). Most developmental policies today prefer the selectionist paradigm in terms of the neoliberal free market. The transformational paradigm in development policies was predominant in the era of the welfare state in the West, and its counterpart in the era of the statism of the East. Sustainable development in a socio-cultural sense is the youngest and the least consistent policy concept, and it is not founded on the evolution paradigms. The concept was launched by the UN as an attempt at mediating, mostly on the grounds of ecological alarms, between the free-market and statist policies. The author considers the hybridization of these two paradigms to be a proper conceptual foundation of sustainable development. On this premise, he expounds the concept of a culturally oriented sustainable development, arguing that hybrids of developmental policies are more suitable for a decent survival of most countries